# qchem question again

#### dontbam

##### Member
10+ Year Member
5+ Year Member
hey guys can you help me with this question from kaplan:

Q: The solubility of CaF2 (Ksp = 4 x 10^-11) in a 0.1M solution of Ca(No3)2 is approximately:

A: 4 x 10^-11 M
B: 2 x 10^-11 M
C: 1 x 10^-5 M
D: 5 x 10^-6 M
E: None of these bad boys

answer is C, can anyone explain?

#### dat_student

##### Junior Member
10+ Year Member
5+ Year Member
dontbam said:
hey guys can you help me with this question from kaplan:

Q: The solubility of CaF2 (Ksp = 4 x 10^-11) in a 0.1M solution of Ca(No3)2 is approximately:

A: 4 x 10^-11 M
B: 2 x 10^-11 M
C: 1 x 10^-5 M
D: 5 x 10^-6 M
E: None of these bad boys

answer is C, can anyone explain?
CaF2 <--> Ca2+ + 2F-
......(approx. 0.1) + 2S

(A) Ksp = (0.1)(2S)^2 = 4 * 10^-1 * S^2
(B) Ksp = 4 * 10 ^-11
(A) & (B) >> 4 * 10^-1 * S^2 = 4 * 10 ^-11

S^2 = 10^-10
S = 10^-5 (Answer choice C)

OP
D

#### dontbam

##### Member
10+ Year Member
5+ Year Member
wait i dont really get how you come up with these numbers, can you explain it ? thx

dat_student said:
CaF2 <--> Ca2+ + 2F-
......(approx. 0.1) + 2S

(A) Ksp = (0.1)(2S)^2 = 4 * 10^-1 * S^2
(B) Ksp = 4 * 10 ^-11
(A) & (B) >> 4 * 10^-1 * S^2 = 4 * 10 ^-11

S^2 = 10^-10
S = 10^-5 (Answer choice C)

#### Envision

##### Envisioning...
10+ Year Member
7+ Year Member
dontbam said:
wait i dont really get how you come up with these numbers, can you explain it ? thx

CaF2 -> Ca + 2F

from this, set up your solubility equation. what you are given is the solubility constant (ksp), and the solubility of Ca (.1 M). this is testing your knowledge of the common ion effect, because there is already .1M of Ca from Ca(NO3)2, it will be less soluble than if it was in water. anyway, the equation is as follow:

ksp= [Ca][2x]^2 the 2x is because of the stoichmetric coeficient, notice there is 2F for every 1 Ca.

from here, you already know ksp, and Ca is ~.1M. although there is a small amount due to CaF2, it plays a very small role so most will be from 0.1 M from Ca(no3)2.

4x10^-11=[.1][2x]^2....x=1x10^-5 (c)

hope that helps.